The Blueprint : Conservative Parties and their Impact on canadian Politics. - Lewis, J. P.; Everitt, Joanna (Toronto : University of Toronto Press, 2017)
In this collection, J.P. Lewis and Joanna Everitt bring together a group of up-and coming-political scientists as well as senior scholars to explore the recent history of the Conservative Party of Canada, covering the pre-merger period (1993-2003) and both the minority and majority governments under Prime Minister Stephen Harper.
14 Stephen Harper and the Radicalization of Canadian Foreign Policy15 Conclusion: A Moderate Turn to the Right with At Least One Enduring Consequence; Contributors; Index.
Print version record.
Includes bibliographical references and index.
Text in English.
eBooks on EBSCOhost
Keywords: Conservative Party of Canada ( -1942); Parti conservateur du Canada; Conservative Party of Canada ( -1942); Conservatism -- Canada; Canada -- Politics and government -- 1993-2006.; Conservatisme -- Canada; POLITICAL SCIENCE -- Political Process -- Elections; POLITICAL SCIENCE -- Political Process -- General; POLITICAL SCIENCE / History & Theory; Conservatism; Canada; Electronic books